Legal Construction of Surrogacy in Indonesia Based on The Altruistic Regulation Model in Australia - Alya Sakila (Law Research Review Quarterly, 2026)
Although Indonesia has regulated provisions regarding assisted reproductive technology, there are no regulations that explicitly regulate the legality, mechanisms, or legal consequences of surrogacy. This condition creates legal uncertainty that has various implications for the protection of parties involved in the practice of surrogacy. This study aims to analyze the implications of the legal vacuum of surrogacy in Indonesia and examine the principles of altruistic surrogacy regulation in the Australian legal system to serve as a basis for constructing Indonesian national law. This study uses a doctrinal (normative) legal research method with a statutory approach and a conceptual approach. The results show that the legal vacuum of surrogacy in Indonesia has implications for weak legal protection for parties involved in the practice of surrogacy, including surrogate mothers, couples using surrogacy services, and surrogacy-related children. In addition, this study found that the regulation of altruistic surrogacy in the Australian legal system contains several important principles, such as the prohibition of commercial surrogacy, the principle of the best interests of the child, free and informed consent of the parties, state supervision, and certainty of the child's legal status.